محاضرات الكيمياء اللاعضوية للسنة الثانية كيمياء عضوية - (:unkn) unknown (My University, 2024)
تهدف هذه المطبوعة إلى تزويد الطلاب بأساس متين في علم البلورات، وتمكينهم من فهم المفاهيم الأساسية وتطبيقها في دراساتهم المستقبلية.حيث تعتبر البلورات لبنة أساسية في فهمنا للمادة والعالم من حولنا. هذه المطبوعة تقدم نظرة شاملة لعلم البلورات، بدء ا من التعريف الأساسي وصو لً إلى التطبيقات العملية . تحتوي المطبوعة على خمس المحاور الأساسية التالية:  المحور الأول : بعنوان عموميات حول علم البلورات يشرح هذا المحور المفاهيم الأساسية مثل الأنظمة البلورية، الشبكات البلورية، والمستويات الشبكية. كما يتطرق إلى مفهوم الفراغات العكسية الذي يلعب دو را ها ما في دراسة البلورات .  المحور الثاني:بعنوان تراص الذرات يستكشف هذا المحور كيف ترتص الذرات داخل البلورات لتشكل بنى منتظمة، وكيف تؤثر هذه الترتيبات على خواص المادة .  المحوران الثالث و الرابع : بعنوان البنى المعدنية والأيونية يرك زان على دراسة البنى البلورية الشائعة للمعادن والمركبات الأيونية، مثل البنية المكعبة، السداسية، والأنواع المختلفة من البنى الأيونية .  المحور الخامس : بعنوان الإشعاع البلوري يشرح هذا المحور كيف تستخدم الأشعة السينية لدراسة البنى البلورية، وكيف يتم تحليل بيانات حيود الأشعة السينية لتحديد بنية البلورة . This textbook aims to provide students with a solid foundation in crystallography, enabling them to grasp fundamental concepts and apply them in their future studies. Crystals are the building blocks of matter and understanding their structure is essential to comprehending the world around us. This comprehensive textbook delves into crystallography, starting from basic definitions and progressing to practical applications. The textbook is divided into five main chapters: 1. Fundamentals of Crystallography: This chapter explains core concepts such as crystal systems, crystal lattices, and crystal planes. It also introduces the concept of reciprocal space, which plays a crucial role in crystallography. 2. Atomic Packing: This chapter explores how atoms arrange themselves within crystals to form ordered structures and how these arrangements influence the properties of materials. 3. Metallic and Ionic Structures: Chapters 3 and 4 focus on the study of common crystal structures in metals and ionic compounds, including cubic, hexagonal, and various types of ionic structures. 4. Crystal Diffraction: This chapter explains how X-rays are used to study crystal structures and how X-
مطبوعة بيدغوجية تخصص كيمياء عضوية موجه لطلبة ثانية كيمياء عضوية
Keywords: الكيمياء اللاعضوية،; البلور; الأشعة; البنى المعدنية; NATURAL SCIENCES::Chemistry::Inorganic chemistry; crystallography; X-rays; metallic structures; ionic structures